The readiness for independent living among incarcerated adolescents in Malaysia: a conceptual paper - Tamil Chelvam, Thiresyinie; Daud, Mohd Najmi; Dahamat Azam, Mohamad Naqiuddin (Human Resource Management Academic Research Society, 2021)
Each year thousands of adolescents are discharged from incarceration across the nation. The Prison Department, Malaysia shows up that most of the adolescents who were released from the incarceration period infringe again and re-entered the rehabilitation centre. The increasing number of juvenile crimes and the escalating number of adolescents with repeated offences have challenged the effectiveness of existing intervention procedures and policies. By far, the intervention programs implemented at the approved school in Malaysia are mostly based on 'one for all' orientation. All inmates have to go through the same intervention process through this practice regardless of their different cases and background. Yet, little is known on how well incarcerated adolescents are equipped with relevant knowledge and skills to ensure their readiness to integrate with the outside social world upon their release from the approved schools. Given that, their readiness to cope and adapt with their lives upon their release remains elusive. Therefore, the present paper seeks to analyze the strengths and limitations of the existing intervention programs at approved schools in Malaysia. Also, factors contributing to incarcerated adolescents' readiness to reintegrate with society and to live independently, namely, coping resources of his/her needs of support, information, and feedback to delineate the challenges lying ahead, are scrutinized and proposed to improve the existing practices.